USULAN PERBAIKAN KUALITAS PRODUK TOPSIDE MENGGUNAKAN METODE FMEA DI PT. XYZ - Rahmawati Berlyan; Wawan Kurniawan; Indah Permata Sari (Journal of Management Small and Medium Enterprises (SMEs), 2021)
XYZ is a company engaged in fabrication. Quality is very important for the company because it can affect customer satisfaction. In the production process there are still defect problems found on the top side of the structural construction and it affects the quality of the part. The failure rate on the topside product has a 5:28% percentage exceeds the standards set by the company which is 2%. Based on the percentage of defects that have been obtained, the problem can be solved by fishbone analysis and FMEA. In the first stage using CTQ which aims to identify failures that occur and determine quality characteristics. The next step after identifying the failure that occurred can be calculated DPMO and Sigma Level. After getting the DPMO value and the Sigma level, identification of the root causes of the failure occurred. The causes of problems that have been analyzed using fishbone analysis can be solved using FMEA. Keywords : DPMO, Tingkat Sigma, Fishbone analysis, FMEA